PERANAN SAKSI AHLI FORENSIK DALAM PENETAPAN TERSANGKA TINDAK PIDANA PEMBUNUHAN (Studi Polres Labuhanbatu) - Poriaman, Poriaman; Hakim, Abdul; Siregar, Risdalina (Jurnal Ilmiah Advokasi, 2021)
In a trial examination of a criminal case, the judge conducts an examination with at least two valid pieces of evidence and also pays attention to the indictment of the public prosecutor regarding what criminal act the defendant has committed. In the case of murder the judge needs a forensic expert to find out what caused the criminal incident. The forensic doctor's statement in the form of a visum et repertum plays a role in deciding / imposing a sentence for the convicted person, because the Visum Et Repertum contains information or information about the causes that resulted in a person's death or injury. The formulation of the problems in this study are: 1. What is the role of forensic experts in uncovering the crime of murder? 2. What are the obstacles faced by forensic experts in uncovering the crime of murder? This study used a normative approach, the research material was collected using document study techniques, and data analysis techniques were used qualitatively. The results of the research show that: 1. The role of a forensic specialist is very important in uncovering the crime of murder, namely being able to directly provide information in court in the form of visum et repertum. 2. The judge's consideration of the results of the forensic doctor's testimony in court in revealing the crime of murder is very helpful for the judge in taking a legal consideration.Keywords: Witness; forensic expert; Criminal act; Suspect; Murder.